Imagining the Future: Future Imagination Training Decreases Delay Discounting Among Internet Addicts and Non-Problematic Users - Li, Hongxia (Frontiers in Psychology, 2021)
To test whether future imagination can reduce internet addicts’ delay discounting rate, we recruited 40 internet addicts (treatment sample) and 39 non-problematic users (control sample). We used a 2 (participant type: individuals with Internet addiction vs. non-problematic users) × 2 (training type: future event imagination training vs. control condition) × 2 (training session: first session vs. final session) mixed-subjects design to test our hypothesis. Participant type and training type were between subject and training session was within subject. Half of each sample (internet addicts and non-problematic users) was randomly assigned to complete five sessions of future imagination training and the other half was assigned to describe some daily events they had observed. We used the Barratt Impulsivity Scale and Delay Discounting Task to assess our outcome variable, including addiction, impulsivity and delay discounting rate. We used SPSS Version 16.0 to analyze our experimental data. The results showed that future imagination training significantly reduced the delay discounting rate (also for impulsivity and addiction) for both internet addicts and non-problematic users than control condition. Besides, the negative effect of future imagination training on delay discounting rates (also for impulsivity and addiction) remained consistent across the five training sessions. These findings suggest that future imagination training can be a useful approach to reduce impulsivity among those who are addicted to internet.